Influence of high intensity focused ultrasound on the microstructure and c-di-GMP signaling of Pseudomonas aeruginosa biofilms - Bharatula, LD; Marsili, E; Rice, SA; Kwan, JJ (Frontiers Media, 2020)
Bacterial biofilms are typically more tolerant to antimicrobials compared to bacteria in the planktonic phase and therefore require alternative treatment approaches. Mechanical biofilm disruption from ultrasound may be such an alternative by circumventing rapid biofilm adaptation to antimicrobial agents. Although ultrasound facilitates biofilm dispersal and may enhance the effectiveness of antimicrobial agents, the resulting biological response of bacteria within the biofilms remains poorly understood. To address this question, we investigated the microstructural effects of Pseudomonas aeruginosa biofilms exposed to high intensity focused ultrasound (HIFU) at different acoustic pressures and the subsequent biological response. Confocal microscopy images indicated a clear microstructural response at peak negative pressures equal to or greater than 3.5 MPa. In this pressure amplitude range, HIFU partially reduced the biomass of cells and eroded exopolysaccharides from the biofilm. These pressures also elicited a biological response; we observed an increase in a biomarker for biofilm development (cyclic-di-GMP) proportional to ultrasound induced biofilm removal. Cyclic-di-GMP overproducing mutant strains were also more resilient to disruption from HIFU at these pressures. The biological response was further evidenced by an increase in the relative abundance of cyclic-di-GMP overproducing variants present in the biofilm after exposure to HIFU. Our results, therefore, suggest that both physical and biological effects of ultrasound on bacterial biofilms must be considered in future studies.